SOCIAL CONSCIOUSNESS IN THREE SHORT STORIES WRITTEN BY LEO TOLSTOY - Faiha Fakhari Mousa Alkayed, (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2024)
The paper presents a discussion of three selected short stories written by Leo Tolstoy namely: “God Sees the Truth but Wait, Three Questions, and What Men Live By”. Thus, the aim of this paper is to reveal the social consciousness as appeared in such literary kind because awareness plays an important role in people's lives and all our lives are built on the awareness of things. However, it has been noticed that this work of Leo Tolstoy mirrors awareness of traditional and modern values and have thematic varieties, deep insight into human realities and characters. The stories of Leo Tolstoy represent an authentic and real picture of human life which considered being a convincing story.